Balance the redox reaction in acidic solution: H^+(aq) + Cr(s) -> H2(g) + Cr^2+(aq). The book answer is: 2Cr(s) + 4H^+(aq) -> 2Cr^2+(aq) + 2H2(g). But I can’t seem to get that answer.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

`H^+ + Cr ->H_2 + Cr^2^+`

Divide both the reaction into two half reactions.

`H^+ -> H_2`

`Cr -> Cr^2^+`

``Balance individual reactions by following oxidation state method.

`2H^+ + 2e^- -> H_2`

`Cr -> Cr^2^+ + 2e^-`

Multiply both the reaction with 2.

`(2H^+ + 2e^- -> H_2)*2` = `4H^+ + 4e^- -> 2H_2`

`(Cr -> Cr^2^+ + 2e^-) * 2` = `2Cr -> 2Cr^2^+ + 4e^-`

Add both the reactions...

`4H^+ + 2Cr -> 2H_2 + 2Cr^2^+`

This is your text book answer... But i beleive there is something missing in your question...

If you post complete question then i would be able to help you with steps.

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial Team